Very Large-Scale Fires 1998
DOI: 10.1520/stp12189s
|View full text |Cite
|
Sign up to set email alerts
|

Boiling Liquid Expanding Vapor Explosions (BLEVE): Possible Failure Mechanisms

Abstract: Detailed re-analysis of the catastrophic failures of four 2-tonne LPG vessels subjected to jet fire attack indicates that the severity of the event and the intensity of the fireballs formed may be a function of the initiating mode of vessel failure and the thermo-hydraulic state of the contents. The mechanism of vessel failure appears to be a two-step process; the formation of an initiating overpressure crack in the high temperature vapor wetted walls of the vessel, followed by a final catastrophic ‘unzipping’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…McDevitt et al [15], Prugh [16,17], Leslie and Birk [18], Lees [3], Birk and Cunningham [2,19], Casal et al [5] and Venart [20], among others, have given elaborate description of the occurrences which lead to a BLEVE. Based on their observations, and of Reid [21], Shebeko et al [22] and Birk et al [23], the steps involved in a typical BLEVE can be identified as under:…”
Section: Mechanism Of Blevementioning
confidence: 99%
See 1 more Smart Citation
“…McDevitt et al [15], Prugh [16,17], Leslie and Birk [18], Lees [3], Birk and Cunningham [2,19], Casal et al [5] and Venart [20], among others, have given elaborate description of the occurrences which lead to a BLEVE. Based on their observations, and of Reid [21], Shebeko et al [22] and Birk et al [23], the steps involved in a typical BLEVE can be identified as under:…”
Section: Mechanism Of Blevementioning
confidence: 99%
“…The size, the life, and the radiation intensity of a fireball may also depend on the temperature of the liquid lading [31], and whether the loss of confinement of the flammable material had occurred when the pressure inside was still rising [32]. The BLEVE fireballs are spheroidal when fully developed; on liftoff they acquire a mushroom-like shape.…”
Section: Mechanism Of Blevementioning
confidence: 99%
“…Several researchers have published articles concerning the diverse aspects of these accidents, such as the mechanisms of explosions [1], the influence of thermal stratification [2], and the behavior of ejected fragments [3]. Our knowledge about the phenomenon has significantly improved, although not sufficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Such fireballs can be very large, causing a very strong thermal radiation [26,27]. The size, the life, and the radiation intensity of a fireball may also depend on the temperature of the liquid lading [28], and whether the loss of confinement of the flammable material had occurred when the pressure inside was still rising [29]. The BLEVE fireballs are spheroidal when fully developed; on liftoff they acquire a mushroom-like shape.…”
Section: There Is Fireball or Toxic Dispersionmentioning
confidence: 99%
“…and Birk[15], Lees[3], Birk and Cunningham[2,16], Casal et al[5] and Venart[17], among others, have given elaborate descriptions of the occurrences which lead to a BLEVE. Based on their observations, and of Reid[18], Shebeko et al[19] and Jim Smith (left) and Bill Walls who, along with Bill Marsh had introduced the term BLEVE and had given the initial explanation of its mechanism (Photo courtesy Ms Roberta, daughter of MrWalls) Birk et al[20], the steps involved in a typical BLEVE(Fig.…”
mentioning
confidence: 99%